The Efficacy of Targeted Sanctions in Enforcing Compliance with International Law. (2019) - Hofer, Alexandra
Abstract : In the international legal order, sanctions are valued for their coercive and stigmatizing functions. Through the imposition of financial or other costs, these measures seek to induce compliance with international law by those who are targeted. They also aim to signal the sender's commitment to the violated norm and stigmatize an actor responsible for wrongful behavior. In light of these functions, this essay examines the factors to assess when evaluating the efficacy of unilateral targeted sanctions in enforcing international law. The issue is relevant not only for political scientists, but also for international lawyers interested in ensuring compliance with international norms.